The Ashgate research companion to ethics and international relations - Hayden, Patrick 1965- (Ashgate research companion, 2009)
While skepticism about the role of moral considerations in international politics has been influential within the discipline of international relations (IR), those writing on topics such as war, peace, rights and trade up until the twentieth century took seriously the importance of ethical values and moral debates. The 1990s and 2000s have seen a substantial growth of attention to the ways in which IR conceives and analyzes themes of an ethical nature, and how issues, problems and policies involving ethics are addressed by a variety of actors within the international system. This indispensable research companion widens the perspective from 'ethics and international relations' to 'ethics in international relations', redressing the (mis)perception that ethical concepts, principles, norms and rules are not in part constitutive of the international system and the agents acting within that system. Necessarily cross-disciplinary, expertise is drawn from IR and also philosophy, political theory, religious studies, history and law, making this an ideal volume for any library reference collection.--Publisher's description.